(untitled) (Proceedings of the International Conference on Future of Education, 2021)
The purpose of this study is to explore International Baccalaureate Diploma Program (IBDP) alumni’s perceptions of IBDP education as well as to investigate IBDP graduates’ reflections about the extent to which the IBDP education has impacted their university study at the higher education in the Turkish context. The study utilized a survey design analyzed quantitatively (descriptive statistics) and qualitatively (content analysis) to collect data from IBDP alumni (N=170 out of 347) who graduated from 2012 to 2019 from a national private school implementing international education in eastern Turkey. The results of the research revealed that participants gained the IB learner profile attributes and learned how to become an internationally-minded individual through the IB education. Specifically, research participants indicated that they gained communicative skills in a foreign language, academic abilities such as researching as well as critical and analytical thinking skills, which were transferred to their post-secondary education. However, participants do not think that they are better prepared for the Turkish university entrance examination through the IBDP education they received in their secondary education. This finding is significant to show the dilemma between international education outcomes and university entrance examination preparation. Students’ well-being is another possible area of investigation in the educational contexts where students are expected to comply with the requirements of both national and international education. These implications are significant for practitioners for IBDP implementation improvements at secondary schools as well as for educators for promoting recognition of international education at post-secondary institutions. Keywords: alumni reflections, international education, International Baccalaureate Diploma Program, impact study, learner profile, post-secondary education